The relationship between swimming performance and achievement goal orientation of young swimmers - Ljødal, I.; Gonjo, T.; Pensgaard, A. M.; Olstad, B. H. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Swimming performance cannot be determined by physiological or biomechanical factors alone. Psychological factors, such as motivation, should also be considered. Load-velocity profiling has shown that front crawl performance is related to theoretical maximum velocity (V0 ) and load (L0 ) (Gonjo et al., 2021). Task goal orientation, based on the Achievement Goal Theory, has been associated with improved performance and increased effort (Roberts et al., 2018). Sixty-seven swimmers aged 11-13 completed the Perception of Success Questionnaire (POSQ) and performed three 25 m semi-tethered swims using the 1080 Sprint. Results showed no significant correlations, suggesting that performance level is independent of motivation at this age. Regardless, the non-significant results should not lead to disregard of goal orientation`s influence on performance through persistence in hard-work and intrinsic enjoyment (Roberts et al., 2018).